2009
DOI: 10.1111/j.1461-0248.2009.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore metabolism and stoichiometry each constrain herbivory at different organizational scales across ecosystems

Abstract: Plant-herbivore interactions mediate the trophic structure of ecosystems. We use a comprehensive data set extracted from the literature to test the relative explanatory power of two contrasting bodies of ecological theory, the metabolic theory of ecology (MTE) and ecological stoichiometry (ES), for per-capita and population-level rates of herbivory across ecosystems. We found that ambient temperature and herbivore body size (MTE) as well as stoichiometric mismatch (ES) both constrained herbivory, but at differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
196
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(204 citation statements)
references
References 88 publications
(184 reference statements)
7
196
1
Order By: Relevance
“…In their meta-analysis across different systems and organism groups, Hillebrand et al [21] generally found increasing per capita grazing rates with decreasing food quality, but decreasing population grazing rates. The capacity of individual consumers to increase food uptake rstb.royalsocietypublishing.org Phil.…”
Section: (I) Population Grazing Ratesmentioning
confidence: 99%
See 4 more Smart Citations
“…In their meta-analysis across different systems and organism groups, Hillebrand et al [21] generally found increasing per capita grazing rates with decreasing food quality, but decreasing population grazing rates. The capacity of individual consumers to increase food uptake rstb.royalsocietypublishing.org Phil.…”
Section: (I) Population Grazing Ratesmentioning
confidence: 99%
“…Grazing and growth rates of consumers depend on the body mass, food stoichiometry and temperature [21,27]. It has been shown that the weight-specific grazing rate scales with a grazer's body mass as m 20.25 [28,29].…”
Section: (C) Theoretical Predictionsmentioning
confidence: 99%
See 3 more Smart Citations